Protic Ionic Liquid Cation Alkyl Chain Length Effect on Lysozyme Structure - Han, Qi (2022)
Solvents that stabilize protein structures can improve and expand their biochemical applications, particularly with the growing interest in biocatalytic-based processes. Aiming to select novel solvents for protein stabilization, we explored the effect of alkylammonium nitrate protic ionic liquids (PILs)-water mixtures with increasing cation alkyl chain length on lysozyme conformational stability. Four PILs were studied, that is, ethylammonium nitrate (EAN), butylammonium nitrate (BAN), hexylammonium nitrate (HAN), and octylammonium nitrate (OAN). The surface tension, viscosity, and density of PIL-water mixtures at low to high concentrations were firstly determined, which showed that an increasing cation alkyl chain length caused a decrease in the surface tension and density as well as an increase in viscosity for all PIL solutions. Small-angle X-ray scattering (SAXS) was used to investigate the liquid nanostructure of the PIL solutions, as well as the overall size, conformational flexibility and changes to lysozyme structure. The concentrated PILs with longer alkyl chain lengths, i.e., over 10 mol% butyl-, 5 mol% hexyl- and 1 mol% octylammonium cations, possessed liquid nanostructures. This detrimentally interfered with solvent subtraction, and the more structured PIL solutions prevented quantitative SAXS analysis of lysozyme structure. The radius of gyration (Rg) of lysozyme in the less structured aqueous PIL solutions showed little change with up to 10 mol% of PIL. Kratky plots, SREFLEX models, and FTIR data showed that the protein conformation was maintained at a low PIL concentration of 1 mol% and lower when compared with the buffer solution. However, 50 mol% EAN and 5 mol% HAN significantly increased the Rg of lysozyme, indicating unfolding and aggregation of lysozyme. The hydrophobic interaction and liquid nanostructure resulting from the increased cation alkyl chain length in HAN likely becomes critical. The impact of HAN and OAN, particularly at high concentrations, on lysozyme structure was further revealed by FTIR. This work highlights the negative effect of a long alkyl chain length and high concentration of PILs on lysozyme structural stability.